Iowa Birdline update, September 9, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for September 9, 1990. Highlights of the update include sightings of a California Gull, a Parasitic Jaeger, a Red Knot, a Red-necked Phalarope, Snowy Egrets, and Barn Owls. Other observations of note were of Little Blue Herons, Cattle Egrets, Baird's Sandpipers as well as numerous shorebird and Warbler species. Epson - sheet feed/flatbed